A combined solution exchange/plunge-freezing device for skinned muscle fibers - Stegmann, Heiko; Fink, Rainer (Journal of muscle research and cell motility, 1999)
For many contractility studies, defined functional states of skinned muscle fiber preparations can be introduced by application of standardized perfusion protocols with large varieties of experimental solutions. Functionally important subcellular element distributions in the myoplasm and in the sarcoplasmic reticulum can be measured with high spatial resolution by electron microscopic microanalysis. Capturing these subcellular ion distributions requires their rapid immobilization by quick-freezing. We therefore combined a plunge-freezing device with a semiautomatic solution exchanger to reproducibly perfuse skinned muscle fiber bundles with multiple solutions. The isometric tension produced is simultaneously recorded as an indicator for the functional state. The samples can be quick-frozen at any chosen time of the tension transient. A cryoglueing technique finally delivers specimens suitable for cryoultramicrotomy.